1998
DOI: 10.1161/01.cir.98.2.175
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Treatment Improves Endothelium-Dependent Hyperpolarization in the Mesenteric Artery of Spontaneously Hypertensive Rats

Abstract: Background-The vascular endothelium releases endothelium-derived hyperpolarizing factor (EDHF). The mesenteric arteries of 6-to 8-month-old spontaneously hypertensive rats (SHRs) exhibit an impairment of the hyperpolarization induced by acetylcholine via EDHF. Methods and Results-We determined whether antihypertensive treatment can improve EDHF-mediated responses inSHRs. Beginning at age 8 to 9 months, the animals were treated with either enalapril (40 mg ⅐ kg Ϫ1 ⅐ d Ϫ1 ) (SHR-Es) or a combination of hydralazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
63
5
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 69 publications
8
63
5
1
Order By: Relevance
“…These authors concluded that enhanced endothelium-dependent relaxation after long-term ACE inhibition might be attributed to increased endothelium-dependent hyperpolarization. The ACh-induced hyperpolarization in the mesenteric arteries of SHR treated with enalapril or a combination of hydralazine and hydrochlorothiazide improved to a level comparable to that in Wistar-Kyoto rats; EDHF-mediated relaxation, as assessed by L-NA-resistant relaxations to ACh, was improved in treated SHR, whereas in the arteries, in which responses to EDHF were blocked by exposure to high K ϩ media, no difference was found in relaxations to ACh among treated and untreated SHR and Wistar-Kyoto rats (Onaka et al, 1998). It was concluded that antihypertensive treatment improved EDHF-mediated hyperpolarization and relaxation in SHR mesenteric arteries, whereas NO-mediated relaxation did not seem to be modulated by drug therapy.…”
Section: G Mesenteric Vasculaturementioning
confidence: 74%
“…These authors concluded that enhanced endothelium-dependent relaxation after long-term ACE inhibition might be attributed to increased endothelium-dependent hyperpolarization. The ACh-induced hyperpolarization in the mesenteric arteries of SHR treated with enalapril or a combination of hydralazine and hydrochlorothiazide improved to a level comparable to that in Wistar-Kyoto rats; EDHF-mediated relaxation, as assessed by L-NA-resistant relaxations to ACh, was improved in treated SHR, whereas in the arteries, in which responses to EDHF were blocked by exposure to high K ϩ media, no difference was found in relaxations to ACh among treated and untreated SHR and Wistar-Kyoto rats (Onaka et al, 1998). It was concluded that antihypertensive treatment improved EDHF-mediated hyperpolarization and relaxation in SHR mesenteric arteries, whereas NO-mediated relaxation did not seem to be modulated by drug therapy.…”
Section: G Mesenteric Vasculaturementioning
confidence: 74%
“…In mesenteric arteries obtained from spontaneously hypertensive rats (SHRs), both a markedly reduced EDHF-mediated relaxation and a reduced EDHFmediated hyperpolarization have been observed, by comparison with those in arteries from age-matched normotensive Wistar-Kyoto rats (54). The finding that these responses could be restored by an ACEI, by an ARB, or by a combination of the two has been taken as an indication of the negative influence of the RAS on EDHF-mediated responses (54,55). Indeed, in a very recent study, Dal-Ros et al (56) demonstrated in the rat that Ang II-induced hypertension is associated with selective impairments of EDHF-mediated relaxation and hyperpolarization in the mesenteric artery.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[23][24][25] Although NO-mediated responses are relatively easy to evaluate, the main difficulty in investigating alterations in EDHF-mediated relaxations is related to the fact that different types of EDHF appear to exist and indeed may act in parallel. Currently, the only feature shared by all of the EDHFs described is the exquisite sensitivity of responses to the combination of charybdotoxin and apamin.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Moreover, treatment of hypertension improves endothelium-dependent relaxation by increasing the NO-mediated and the EDHF-mediated relaxation. 4,5 Endothelial dysfunction in hypertension has been linked to a decrease in NO bioavailability reflecting the impaired generation of NO and/or the enhanced scavenging and inactivation of NO by oxygen-derived free radicals. 6,7 The mechanisms leading to the attenuation of EDHF-mediated relaxations in hypertension are poorly understood but are reportedly unrelated to enhanced vascular oxidative stress.…”
mentioning
confidence: 99%